Revaluasi Aset Tetap pada Perusahaan Sektor Industri Manufaktur Di Indonesia - Chandra Ferdinand Wijaya (Jurnal Akuntansi, 2021)
IFRS was formed which is expected to improve the quality of financial reporting and enchance comparability of financial information for decision making. Indonesia is one of the countries that adopted IFRS. One of the IFRS standard adopted by Indonesia is the fixed assets accounting standard as outlined in PSAK 16. PSAK 16 explains that the measurement of fixed assets can be done by choosing between cost models or revaluation models. This study is intended to provide development of fixed asset measurement models that tend to be used by the manufacturing companies in Indonesia along with the reasons underlying to apply the related fixed asset measurement model. This research is an analytical descriptive study conducted on manufacturing companies listed on the Indonesia Stock Exchange from 2015 until 2017. The result shows that most of the manufacturing companies in Indonesia still use the cost model in the measurement of fixed assets for financial reporting. Nonetheless, there are already several manufacturing companies that implement fixed asset revaluation models and the number has increased from year to year. With this in mind, the revaluation model for fixed assets is growing and the role of asset valuation services is felt to be increasingly needed. Keywords: Cost Model, Fixed Asset, IFRS, PSAK 16, and Revaluation Model